Analysis of The Implementation of The Equality Before the Law Principles Against the Perperators of Corruption in the Jurisdiction of the Criminal Court of Corruption at the Surabaya State Court of the Decision Number 119/Pid.Sus.TPK/2018/PN.Sby - Tinuk Dwi Cahyani; Yohana Puspitasari Wardoyo (Alliance of Health Activists (AloHA), 2021)
Corruption that still occurs a lot in Indonesia from year to year, even though it is shown in the perception index that has increased from year to year for the better, is still in a harmful situation for the country. At this time can observe, see and feel that law enforcement is in a position that is can not be trusted. The public questioned the performance of law enforcement officials in eradicating corruption, the spread of judicial mafia, violations of the law in assessing the APBN and APBD among bureaucracy. In 2018 the public was dumbfounded by the mass corruption committed by 41 members of the Malang City DPRD (Regional People's Representative Assembly) during 2018. Malang City is considered the ‘general champion' in the corruption category in the number of suspects. 6 of them have been tried at the Corruption Court at the Surabaya District Court and have been decided by the Panel of Judges as in Decision Number 119/Pid.Sus.TPK/2018/PN.Sby with different sentences. How is the application of the principle of equality before the law against perpetrators of Corruption in the jurisdiction of the corruption court at the Surabaya District Court against the Decision Number 119/Pid.Sus.TPK/2018/PN.Sby? The research method used is the normative legal research method. The results of the research show that the judicial process in handling corruption crimes is in accordance with the rules regarding the types of punishment in the Corruption Crime Court and meets the principle of equality before the law. Keywords: corruption; equality before the law; Malang